2022
DOI: 10.1109/tnsre.2022.3204781
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Upper-Limb Brunnstrom Recovery Stage Evaluation via Daily Activity Monitoring

Abstract: Motor function assessment is crucial for post-stroke rehabilitation. Conventional evaluation methods are subjective, heavily depending on the experience of therapists. In light of the strong correlation between the stroke severity level and the performance of activities of daily living (ADLs), we explored the possibility of automatically evaluating the upperlimb Brunnstrom Recovery Stage (BRS) via three typical ADLs (tooth brushing, face washing and drinking). Multimodal data (acceleration, angular velocity, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Brunnstrom Scale [ 7 , 17 ]: upper limb and hand parts; each is divided into stage I–VI, and the higher the level, the better the motor function. Stage I: no exercise; Stage II: slight flexion; Stage III: flexion but not extension; Stage IV: the thumb can be pinched and loosened, and the fingers can be extended semi-randomly in a small area; Stage V: can do spherical or cylindrical grip, and can be free to extend the whole finger, but the range of size is not equal; Stage VI: full range extension of various grips, but with less speed and accuracy than the healthy side.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brunnstrom Scale [ 7 , 17 ]: upper limb and hand parts; each is divided into stage I–VI, and the higher the level, the better the motor function. Stage I: no exercise; Stage II: slight flexion; Stage III: flexion but not extension; Stage IV: the thumb can be pinched and loosened, and the fingers can be extended semi-randomly in a small area; Stage V: can do spherical or cylindrical grip, and can be free to extend the whole finger, but the range of size is not equal; Stage VI: full range extension of various grips, but with less speed and accuracy than the healthy side.…”
Section: Methodsmentioning
confidence: 99%
“…The above evaluation methods have been widely used in clinical practice for a long time, and their reliability and validity are also widely recognized. However, the actual application is easily influenced by personal experience [ 6 , 7 , 8 , 9 ]. Therefore, there is great interest in developing an automated system to achieve intelligent, objective and quantitative assessment of hand function rehabilitation after stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, timely rehabilitation assessment of rehabilitation training can effectively reduce the impact of motion compensation and muscle fatigue. Presently, upper limb rehabilitation assessment methods, including Brunnstrom Recovery Stage ( Meng et al, 2022 ), Fugl-Meyer Assessment ( DJ, 2002 ), and Modified Ashworth Scale ( Ansari et al, 2012 ), possess comprehensive evaluation criteria. They heavily rely on clinical expertise and possess subjectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Doherty et al [ 28 ] used the context provided by cameras to identify the specific classed of activity once an accelerometer had identified the level of activity being undertaken. Meng et al [ 29 ] collected acceleration, angular velocity, and surface electromyography data synchronously from 5 upper-limb-worn sensor modules to evaluate the upper-limb Brunnstrom Recovery Stage (BRS) via three typical ADLs (tooth brushing, face washing, and drinking). Second, several studies have revealed that using a single accelerometer might not be sufficient for activity classification [ 24 , 30 ].…”
Section: Introductionmentioning
confidence: 99%